First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations THE PEOPLE'S LEAGUE OF HEALTH. INCOME AND EXPENDITURE ACCOUNT, from 1st January to 31st December, 1921, inclusive. EXPENDITURE. To OFFICE EXPENSES, viz. : £ s. d. £ s. d. Rent 170 7 3 Caretaker 26 2 0 Coal and Light 14 16 6 Insurances 10 9 Salaries 276 10 0 National Health and Unemployment Insurance 2 1 6 Travelling Expenses 4 11 4 Postages and Telegrams 40 2 3 Telephone 20 3 5 Printing and Stationery 48 11 3 Repairs. Office Sundries, etc. 25 11 9 629 8 0 „ PROPAGANDA EXPENSES, VIZ. : Expenses of Meetings and Expenses 27 18 6 Lecturers 10 13 8 Do. Sims Woodhead Series 95 6 6 Reporters' Fees 6 15 4 Efficiency Exhibition Expenses 186 13 8 Publications 6 11 7 Pamphlets 11 14 0 Badges 10 13 9 356 7 0 „ SUNDRIES : Law Costs 12 0 0 Depreciation of Typewriter 5 0 0 17 0 0 1,002 15 0 „ BALANCE, carried to Balance Sheet 1,278 15 10 £2,281 10 10 INCOME. £ s. d. By NET PROCEEDS OF NATIONAL SUNDAY LEAGUE CONCERT, 11th December, 1921 236 0 0 „ DONATIONS RECEIVED 562 2 8 „ SUBSCRIPTIONS — Members' 24 18 0 „ BANK INTEREST 7 4 3 „ NET PROCEEDS OF DEVONSHIRE HOUSE BALL 1,451 5 11 £2,281 10 10 200/B/3/2/C693/1/71